2021
DOI: 10.3390/pharmaceutics13050594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Magnesium, Calcium, and Aluminum Chelation on Fluoroquinolone Absorption Rate and Bioavailability: A Computational Study

Abstract: Fluoroquinolones (FQs) are a widespread class of broad-spectrum antibiotics prescribed as a first line of defense, and, in some cases, as the only treatment against bacterial infection. However, when administered orally, reduced absorption and bioavailability can occur due to chelation in the gastrointestinal tract (GIT) with multivalent metal cations acquired from diet, coadministered compounds (sucralfate, didanosine), or drug formulation. Predicting the extent to which this interaction reduces in vivo antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 83 publications
1
11
0
1
Order By: Relevance
“…Higher CIP release from porous PCL film on a glass substrate is observed. The loaded PCL film reveals a burst release of ~50% of the entire load during the first 2 h of immersion followed by the release of the remaining load (up to 80–97% of the total) over 48 h. However, in the case of HCC + CIP, a gradual release over time is observed, with only 64% of the load released over the period of 240 h. The possible reason of this may be associated with the fact that Mg 2+ and Ca 2+ cations, liberated from the HHC and the substrate, are chelating with CIP 0 (zwitterionic form, Figure S3 ) leading to the formation of insoluble chelates in the physiological medium [ 19 ] and reducing the CIP release. This observation is in good agreement with other reports where the complexation of different cations present in physiological media with CIP was shown, reducing the bioavailability of the drug [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher CIP release from porous PCL film on a glass substrate is observed. The loaded PCL film reveals a burst release of ~50% of the entire load during the first 2 h of immersion followed by the release of the remaining load (up to 80–97% of the total) over 48 h. However, in the case of HCC + CIP, a gradual release over time is observed, with only 64% of the load released over the period of 240 h. The possible reason of this may be associated with the fact that Mg 2+ and Ca 2+ cations, liberated from the HHC and the substrate, are chelating with CIP 0 (zwitterionic form, Figure S3 ) leading to the formation of insoluble chelates in the physiological medium [ 19 ] and reducing the CIP release. This observation is in good agreement with other reports where the complexation of different cations present in physiological media with CIP was shown, reducing the bioavailability of the drug [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that CIP presents an inhibiting effect on the corrosion behaviour of PEO-coated Mg. In this work, this effect could be associated with the formation of insoluble chelates such as Mg/Ca-CIP o [ 19 ] ( Figure S3 ) that could precipitate in the cracks and pores of the PEO coating blocking the access of the corrosive species of the medium. The complexation of these compounds is predicted to be thermodynamically favourable at neutral pH as it was reported in works of pharmacokinetics of the fluoroquinolone group to which CIP belongs [ 12 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, transport into the cell is connected with the size of the molecule—e.g., a quinolone molecule chelated with Ca 2+ or Mg 2+ . Such a complex molecule cannot enter the cell because of the bulky size [ 51 ]. The effect of greater sensitivity of Gram-positive bacteria to the examined compounds is also consisted with those reported for other 2-thiohydantoins derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…It is revealed that the bacterial resistance to quinolones might be driven by an increase in the expression of efflux pumps and the decreases of certain outer membrane proteins such as porins as well as the residue mutations of target enzymes in the quinolone resistance determining region, which especially play a vital role in preventing the formation of the ion bridge with 3-carboxyl and 4-carbonyl groups to render quinolones with ineffective antibacterial behavior . The increasingly growing multidrug resistance reflects a global issue creating superbugs difficult to treat. , Moreover, some side effects such as the metal chelation and the retroaction with alkaline drugs also result from the 3-carboxyl group of quinolones. It is of great urgency to develop novel therapeutic strategies, antibacterial drugs with high biosafety, and even targets to counteract the growing multidrug resistance in animal husbandry. , …”
Section: Introductionmentioning
confidence: 99%